PL.37 Maternal Adiposity and Caesarean Section. (26th April 2013) - O'Dwyer, V; Kent, E; JLK, Hogan; O'Connor, C; Farah, N; Turner, MJ
Abstract : Maternal obesity and rising caesarean section (CS) rates are important obstetric issues. High visceral fat (VF) is associated with an increased risk of medical conditions outside pregnancy and gestational diabetes mellitus. The purpose of the study was to assess risk of CS using VF as a marker for maternal obesity and to compare it with Body Mass Index (BMI) as a predictor. Women were recruited following ultrasound confirmation of a singleton first trimester pregnancy. Maternal VF was measured using Bioelectrical Impedance Analysis (BIA). Maternal BMI was measured. Data was analysed using SPSS. Of the 3000 women recruited, 2825 women subsequently delivered a baby weighing >500 g. There were 45.9% primigravidas and 17.6% were obese. The CS rate was 21.4%. VF in the 3 rd and 4 th quintiles was associated with an odds ratio for CS of 1.6 (95% CI 1.3–2.1) and 2.2 (95% CI 1.7–2.9) respectively (p < 0.001). BMI in the 3 rd and 4 th quintiles was associated with an OR for CS of 1.5 (95% CI 1.2–2.0) and 2.3 (95% CI 1.7–3.3) respectively (p < 0.001). After controlling for parity, previous CS and birth weight the ORs were 1.8 (95% CI 1.3–2.4) and 2.3 (95% CI 1.7–2.1) for the 3 rd and 4 th quintiles for VF (p < 0.001). The adjusted ORs for CS were 1.6 (95% CI 1.2–2.3) and 2.4 (95% CI 1.7–3.4) when the 3 rd and 4 th quintiles for BMI were used. Maternal obesity is associated with an increased risk of CS. Maternal adiposity measured by BIA is as good a predictor of the risk of CS as BMI.